CHIT1 and DDAH1 levels relate to amyloid-related imaging abnormalities risk profile in Alzheimer’s disease patients - Marlies Oosthoek; Everard G.B. Vijverberg; Elena R. Blujdea; Sjors G.J.G. In’t Veld; Martín Pucheu Avilés; Sára E. Zsadanyi; Yanaika S. Hok-A-Hin; Allerdien Visser; Wiesje M. van der Flier; Frederik Barkhof; Marta del Campo; Martijn C. Schut; et al. (Alzheimer’s Research & Therapy)
Abstract Background Amyloid-related imaging abnormalities (ARIA) are a common and potentially dangerous side effect in anti-amyloid therapies, creating a need for tools to assess ARIA risk. Several patient factors have been linked to ARIA; namely the presence of microbleeds (MBL+), APOE E4 carriership (APOE4+), and extremely low CSF Aβ42 concentrations (AL). We hypothesize that studying the CSF proteome of Alzheimer’s disease (AD) dementia patients from a high-risk group (MBL+APOE4+AL) can inform on the biological underpinnings of ARIA risk and aid the progress of ARIA risk biomarkers. Methods We utilized CSF proteomic data of AD (n = 156) and cognitively unimpaired individuals (CU n = 100) of the Amsterdam Dementia Cohort. The proteome of the defined high-risk (n = 13) was compared to low-risk AD group (n = 23), using age and sex corrected linear regressions followed by gene ontology analysis. For biomarker prioritization, we selected proteins that were abnormal in the high-risk group versus low-risk and CU patients. The biomarkers were validated in an independent cohort (high risk n = 14, low risk n = 9) analyzed using customized multiplex panels. Lastly, we assessed biomarker lead co-expression. Results Ninety-four proteins differentiated in the high-risk group compared to low-risk (p < 0.05), none surviving FDR correction. These proteins were enriched for synapse-related proteins and axonogenesis. CHIT1 (vs. low-risk AD: FC = 1.0, p = 0.014, vs. CU: FC = 2.4, p < 0.001) and DDAH1 (vs. low-risk AD: FC=-0.31, p = 0.046, vs. CU: FC = 0.5, p < 0.001) were prioritized as biomarker. DDAH1 protein changes replicated in an independent cohort (FC=-0.37, p = 0.010), and CHIT1 replicated on a trend level (FC = 0.70, p = 0.104). DDAH1 levels had the highest co-expression with synaptic process, energy utilization and RNA-binding cell signaling related proteins (R > 0.8). Conclusions The findings suggest that in the high risk group, there is a lack of upregulation in synapse and axonogenesis related proteins. High CSF CHIT1 and less increased CSF DDAH1 levels within AD relate to ARIA risk. From the literature, the link to ARIA risk for CHIT1 could be its contribution to innate immunity or vascular amyloid deposition, and for DDAH1 to blood-brain barrier integrity. Biomarker assays are available to assess the potential of CHIT1 and DDAH1 in trials and treatment studies in the clinical setting.